Tolerance and pharmacokinetics of a ciprofloxacin-coated sinus stent in a preclinical model - Cho, Do-Yeon; Hoffman, Kyle; Skinner, Daniel; Mackey, Calvin; Lim, Dong Jin; Alexander, Grant C.; Bae, Chae Yun; Han, Dong Keun; Jun, Ho-Wook; Woodworth, Bradford A. (WILEY, 2017)
Background: Chronic rhinosinusitis (CRS) is often associated with persistent bacterial infection despite the use of systemic antibiotics. Topically administered antibiotics are an alternative strategy, but require effective local concentrations, prolonged mucosal contact time, minor systemic absorption, and minimal depletion. The objectives of the current study were to analyze the in vitro release rate and in vivo drug delivery tolerance and pharmacokinetics of a ciprofloxacin-coated sinus stent (CSS). Methods: The CSS (2 mg) was created from biodegradable poly-D/L-lactic acid. After analyzing in vitro release profile, CSSs were placed unilaterally in maxillary sinuses of 16 rabbits via dorsal sinusotomy. Animals were euthanized between 1 and 3 weeks postoperatively. Ciprofloxacin concentrations in the sinus tissue and plasmas were assessed using high-performance liquid chromatography. Radiological and histological evaluations were performed. Results: In the in vitro release profile, an initial burst release was observed over the first 24 hours, followed by sustained release through the 14-day time point. In the rabbit model, ciprofloxacin was continuously released from the stent up to 3 weeks at doses > 50 ng/mL. Histologic examination found no evidence of inflammation, epithelial ulceration, or bony reaction upon euthanization of the animals at 21 days. Computed tomography also demonstrated no signs of mucosal edema or opacification in the sinus. Conclusion: The CSS was safe in this preclinical model and sustained release was observed in both the in vitro and in vivo analyses. The innovative stent design coated with ciprofloxacin may provide a unique therapeutic strategy for chronic rhinosinusitis (CRS). (C) 2016 ARS-AAOA, LLC.